Vocal fold immobility after thyroidectomy with intraoperative recurrent laryngeal nerve monitoring - Pedro Netto, Irene de (2007)
CONTEXT AND OBJECTIVE: Intraoperative nerve monitoring has emerged as a valuable tool to facilitate recurrent laryngeal nerve identification during thyroid surgery, thereby avoiding its injury. The aim was to evaluate vocal fold mobility in patients who underwent thyroidectomy with intraoperative nerve monitoring. DESIGN AND SETTING: Cohort formed by a consecutive series of patients, at a tertiary cancer hospital. METHODS: The subjects were patients who underwent thyroidectomy using intraoperative laryngeal nerve monitoring, between November 2003 and January 2006. Descriptive analysis of the results and comparison with a similar group of patients who did not undergo nerve monitoring were performed. RESULTS: A total of 104 patients were studied. Total thyroidectomy was performed on 65 patients. Vocal fold immobility (total or partial) was detected in 12 patients (6.8% of the nerves at risk) at the first postoperative evaluation. Only six (3.4% of the nerves at risk) continued to present vocal fold immobility three months after surgery. Our previous series with 100 similar patients without intraoperative nerve monitoring revealed that 12 patients (7.5%) presented vocal fold immobility at the early examination, and just 5 (3.1%) maintained this immobility three months after surgery, without significant difference between the two series. CONCLUSION: In this series, the use of intraoperative nerve monitoring did not decrease the rate of vocal fold immobility.